PERAN KOMUNIKASI EFEKTIF DAN DUKUNGAN KELUARGA DALAM PENCEGAHAN SPEECH DELAY PADA BALITA - Suraya, Citra; Citra Wisuda, Aris; Rusmarita, Rusmarita (Institut Citra Internasional, 2024)
Speech delay in toddlers is a developmental issue that can affect children's communication skills in the future. One important factor that can prevent speech delays is effective communication between parents, caregivers, and children, as well as optimal family support. The aim of this community service program is to enhance the implementation of effective communication and family support in preventing speech delays in toddlers at RSUD Siti Fatimah AZ-Zahra South Sumatera Province, in 2024. The method used in this program includes three main stages: (1) identifying toddlers who are at risk of experiencing speech delays, (2) preparing materials and guidelines for implementing effective communication and the role of the family in preventing speech delays, and (3) educating parents on the implementation of effective communication and family support to prevent speech delays in toddlers. The results of the program implementation showed that 33 toddlers participated, with the majority aged 1-3 years (78.8%) and the remainder aged 3-5 years (21.2%). Most parents showed an increase in knowledge of up to 85.76%. It is hoped that this activity will strengthen their role in supporting their children's communication and language development